HUBUNGAN ANTARA KREATIVITAS GURU DENGAN MINAT BELAJAR SISWA DI SEKOLAH DASAR - Aras, Latri; DH, Satriani; Amran, Muhammad; Dzikru, Nabilah Adz (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
; The problem in this study is the teacher's lack of creativity in the learning process in the classroom so that students lack interest in learning. This research is a quantitative research with the type of correlational research which aims to determine the relationship between teacher creativity and student interest in learning. The results showed that obtained rx = 0.443, the relationship between the two variables was classified at the level of relationship in the "medium" category, because it was in the range 0.40 - 0.599 and the rcount value (0.443) was greater (>) rtable value (0.177), which means H0 rejected and Ha accepted. Based on the analysis of the data above, it can be concluded that teacher creativity will have an impact on students' interest in learning. So, the better the teacher's creativity, the better the student's interest in learning. From these conclusions, the impact resulting from this study is known that the creativity of a good teacher will increase students' interest in learning.